Acoustic phonons in unfilled tetragonal tungsten-bronze crystals. (3rd October 2018) - Buixaderas, E.; Bérešová, P.; Ondrejkovič, P.; Vaněk, P.; Savinov, M.; Bednyakov, P.; Dec, J.; Mareš, D.; Ševčík, M.; Landa, M.
ABSTRACT: We have studied several unfilled tetragonal tungsten-bronze crystals (SBN-35, CBN-28, CBN-30, CBN-32) by differential scanning calorimetry, Brillouin spectroscopy and piezoresponse-force microscopy. The Brillouin backscattering configuration in the c-plates revealed the longitudinal acoustic phonon, which has a frequency near 50 GHz and displays softening when approaching the phase transition in all crystals. The ferroelectric domain structure and the domain size are dependent on the Sr/Ba or Ca/Ba ratios, and on the occupation rate in the channels as shown by the piezoresponse-force microscopy images. A splitting of the longitudinal acoustic phonon was found in SBN-35 in the multidomain sample, but poling of the crystal removed this splitting and just left the phonon with higher frequency.